2015
DOI: 10.1038/nutd.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

A dietary intervention for chronic diabetic neuropathy pain: a randomized controlled pilot study

Abstract: Background:Diabetic neuropathy is a common and often debilitating condition for which available treatments are limited. Because a low-fat plant-based diet has been shown to improve glycemic control in individuals with type 2 diabetes, we hypothesized that such a diet would reduce painful symptoms of diabetic neuropathy.Methods:In this 20-week pilot study, individuals with type 2 diabetes and painful diabetic neuropathy were randomly assigned to two groups. The intervention group was asked to follow a low-fat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
213
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(216 citation statements)
references
References 31 publications
1
213
1
1
Order By: Relevance
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 30% ( n = 21) of the studies were conducted in the USA , with five undertaken in Australia , four conducted in each of Germany , Japan and Spain , and three conducted in each of Denmark , Finland , Sweden , Iran and the Netherlands . Of the included studies, 47 were randomised controlled trials (RCT) , eight were nonrandomised trials , nine were pre–post studies , six were randomised cross‐over trials and one a longitudinal study .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations